Pilot dispatching problem along a maritime corridor: a case study in the St. Lawrence River - Milad Hematian; Jean-François Audy; Mikael Rönnqvist (Journal of Shipping and Trade)
Abstract This study presents a novel decision support process for a pilot dispatching problem in the St. Lawrence River. It integrates a comprehensive set of time-based performance measures, including working time, waiting time, and skill level differences, to optimize fairness and operational efficiency in pilot dispatching. The proposed process employs a weighted multi-objective model and a goal programming solution method to dynamically rank pilots, continuously updating dispatch plans. A year-long case study in the St. Lawrence River, Canada with 1288 vessels and 200 pilots across four stations showed that the proposed decision support process significantly improved workload distribution, reducing waiting times by 14% and enhancing pilot satisfaction. The findings highlight the potential for more balanced and efficient pilot dispatching approach benefiting for both service quality provided to vessels and the pilots themselves by reducing fatigue and improving performance measures.